Пособие к решению задач по сопротивлению материалов учебное пособие для вузов - Миролюбов И. Н. Игорь Николаевич; Енгалычев С. А. Сергей Александрович; Сергиевский Н. Д. Николай Дмитриевич; Алмаметов Ф. З. Фотях Зайнулович (Москва, Высшая школа, 1969)
Исключено из фонда НТБ ТПУ